FORMULATING YOUTUBE ACCOUNTS AS A COLLATERAL OBJECT: A PROGRESSIVE LEGAL PERSPECTIVE - Ni Made Indah Corry Andani; Anak Agung Ayu Ngurah Sri Rahayu Gorda; I Gede Agus Kurniawan (Universitas Syiah Kuala, 2023)
Using a YouTube account as a collateral object is one of the progressive legal policies as YouTube nowadays tends to have economic orientation. This study discusses the legal certainty of setting up a YouTube account as a collateral object from a progressive legal perspective. This is a normative legal research with a conceptual and statutory approach. This research shows that in order to guarantee legal certainty, it is necessary to establish the Financial Service Authority (OJK) Regulation which substantively regulates standards and guidelines for assessing a YouTube account whether or not it can be used as collateral for debt. Using a YouTube account that can be used as collateral for debt must be seen from its positive and negative impacts. It is necessary to diagnose potential problems that might arise in the future; hence there will be no Youtube accounts can be used as debt collateral, as it would need the parameters to be taken as a standard for assessing a sustainable economic value.